2018
DOI: 10.1073/pnas.1812204115
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting correlated molecular-dynamics networks to counteract enzyme activity–stability trade-off

Abstract: The directed evolution of enzymes for improved activity or substrate specificity commonly leads to a trade-off in stability. We have identified an activity–stability trade-off and a loss in unfolding cooperativity for a variant (3M) of Escherichia coli transketolase (TK) engineered to accept aromatic substrates. Molecular dynamics simulations of 3M revealed increased flexibility in several interconnected active-site regions that also form part of the dimer interface. Mutating the newly flexible active-site res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 28 publications
0
69
0
Order By: Relevance
“…For enzymes in particular, previous studies have shown that missense mutations often act pleiotropically in which catalytically enhancing mutations are, on average, moderately destabilizing (6,(10)(11). Consequently, high basal stability can buffer catalytically beneficial but destabilizing mutations (12)(13), allowing fixation.…”
Section: Introductionmentioning
confidence: 99%
“…For enzymes in particular, previous studies have shown that missense mutations often act pleiotropically in which catalytically enhancing mutations are, on average, moderately destabilizing (6,(10)(11). Consequently, high basal stability can buffer catalytically beneficial but destabilizing mutations (12)(13), allowing fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used a previously stabilised variant H192P/A282P/I365L/G506A (4M) as the template for constructing the new library to promote evolvability . Introduction of these same stabilising mutations was recently found to restore the stability loss of another TK variant (S385D/D469T/R520Q) that was engineered to accepted aromatic aldehydes .…”
Section: Resultsmentioning
confidence: 99%
“…Thermal stability and enzyme dynamics : Dalby and coworkers recently described their experience of epistatic (non‐additive) effects from mutations located in distal parts of E. coli transketolase (TK) while attempting to improve its thermal stability . Starting from the wild‐type enzyme, the investigators created several TK variants with single, double, triple and quadruple mutations.…”
Section: Evolving and Engineering Enzymes Based On Dynamicsmentioning
confidence: 99%